Decontamination of laboratory microbiological waste by steam sterilization. - Rutala, W A (1982)
A steam sterilizer (autoclave) was tested to determine the operating parameters that affected sterilization of microbiological waste. Tests involved standardized loads (5, 10 ad 15 lb [ca. 2.27, 4.54, and 6.80 kg, respectively]) contaminated petri plates in autoclave bags placed in polypropylene or stainless steel containers. Thermal and biological data were obtained by using a digital potentiometer and a biological indicator containing spores of Bacillus stearothermophilus, respectively. The transfer of heat was more efficient when smaller loads of microbiological waste were tested and stainless steel rather than polypropylene containers were used. A single bag with the sides rolled down to expose the top layer of petri plates allowed heat to pass better than did a single bag with the top constricted by a twist-tie. The presence of water in the autoclave bag did not significantly improve heat-up time in stainless steel or polypropylene containers. The results of biological tests substantiated the temperature data. When 10 or 15 lb of microbiological waste was exposed to various test conditions, the only condition that ensured the destruction of B. stearothermophilus involved the use of a stainless steel container (with or without water) for 90 min. Autoclaving for 45 min resulted in the destruction of bacteria included in 10 lb (136 +/- 3 plates) or 15 lb (205 +/- 6 plates) of microbiological waste when stainless steel containers with or without water or polypropylene containers with water used, whereas 60 min was required to kill all bacteria if polypropylene containers without water were used.